“It was Trans Hell:” Exploring the Schooling Experiences of Trans and Non-binary Youth in Alberta - Maine, Emilie; Hardy, Teresa; Wells, Kristopher (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
This paper highlights findings from a qualitative research study exploring the schooling experiences of transgender and non-binary youth (ages 14-25) in Alberta. Given the unique legislative and cultural context of each Canadian province/territory, this study focused on the schooling experiences of TNB youth, specifically within the socially conservative context of Alberta and its provincial education system, which, historically, has lagged behind other Canadian provinces/territories in sexual and gender diversity inclusion. This study contributes to a growing body of qualitative research focusing on the unique experiences of TNB students in Canada by investigating the school-based experiences of TNB youth in Alberta to better understand their lived experiences and to inform educational policies and practices within the province. The research findings highlight four key thematic areas: (1) climate and culture, (2) supports, (3) education, and (4) safety, which participants identified as critical factors that influence their experience(s) in educational environments.